Conformation-Sensitive Steroid and Fatty Acid Sites in the Transmembrane Domain of the Nicotinic Acetylcholine Receptor - Fernández Nievas, Gaspar Antonio (2007)
The mechanism by which some hydrophobic molecules such as steroids and free fatty acids (FFA) act as noncompetitive inhibitors of the nicotinic acetylcholine receptor (AChR) is still not known. In the present work, we employ Förster resonance energy transfer (FRET) between the intrinsic fluorescence of membrane-bound Torpedo californica AChR and the fluorescent probe Laurdan using the decrease in FRET efficiency (E) caused by steroids and FFA to identify potential sites of these hydrophobic molecules. Structurally different steroids produced similar changes (DeltaE) in FRET, and competition studies between them demonstrate that they occupy the same site(s). They also share their binding site(s) with FFA. Furthermore, the FRET conditions define the location of the sites at the lipid-protein interface. Endogenous production of FFA by controlled phospholipase A2 enzymatic digestion of membrane phospholipids yielded DeltaE values similar to those obtained by addition of exogenous ligand. This finding, together with the preservation of the sites in membranes subjected to controlled proteolysis of the extracellular AChR moiety with membrane-impermeable proteinase K, further refines the topology of the sites at the AChR transmembrane domain. Agonist-induced desensitization resulted in the masking of the sites observed in the absence of agonist, thus demonstrating the conformational sensitivity of FFA and steroid sites in the AChR.